Inhibition of the RIP3/MLKL/TRPM7 necroptotic pathway ameliorates diabetes mellitus-induced erectile dysfunction by reducing cell death, fibrosis, and inflammation - Niu, Lipan; Yang, Pei; Zhu, Bingbing; Jin, Xiufang; Yang, Chengxia; Zhang, Xijia; Liu, Yulian; Zhang, Rui; Liu, Fengxia (Frontiers in Pharmacology, 2024)
Diabetes mellitus-induced erectile dysfunction (DMED) is a common complication in patients with diabetes mellitus. Necroptosis is regarded as a form of cell death that is intimately associated with the inflammatory response, which is not only initiated by inflammatory factors such as TNF-α, but also triggers the inflammatory cascade through the rupture of the dying cell. There is no definitive study on the role of necroptosis in the the pathological process of DMED. In light of the pathological features of high inflammation levels in DMED patients, we hypothesise that necroptosis may play an important role in the course of DMED. Our study found that the penile tissues of DMED rats showed high levels of necroptosis. Furthermore, the inhibition of necroptosis with a receptor-interacting protein kinase 3 (RIP3) inhibitor or Yimusake (a common herbal remedy for ED) rescued damage to corpus cavernosum smooth muscle cells (CCSMC) under high glucose conditions. Mechanistically, in vivo experiments have demonstrated that RIP3 can recruit and promote mixed lineage kinase domain like protein (MLKL) phosphorylation, leading to the activation of transient receptor potential melastatin 7 (TRPM7) and triggering *